Challenges of digital preservation for library collection : literature review - Ninditha Aishah Budiarsih; Rifqah Azizah; Zulfatun Sofiyani (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study explores the main challenges in the digital preservation of library collections and utilises the DCC Curation Lifecycle Model to identify structural weaknesses. Through a literature review method, this study compiles and examines the latest literature discussing technological vulnerabilities, metadata inconsistencies, organisational limitations, legal issues, and the lack of digital curation skills among library staff. The results of the analysis show that format obsolescence, storage media instability, the absence of a comprehensive policy framework, and inadequate professional capacity are factors that consistently hinder the sustainability of digital collections. When mapped using the DCC framework, these obstacles appear in the stages of Preservation Planning, Description and Representation Information, Curate and Preserve, and Access, Use, and Reuse, indicating that preservation issues are systemic and interrelated. This study concludes that digital preservation management needs to be designed as an integrated institutional strategy that includes policy strengthening, competency development, durable infrastructure development, and legal management. In general, the results of the study confirm that digital preservation is an organisational mandate that must be carried out continuously through collaboration.